Gingival diseases: plaque induced and non-plaque induced: Penyakit gingiva: induksi plak dan induksi non-plak - Daniel Tetan-el; Andi Mardiana Adam; Eri Hendra Jubhari (Makassar Dental Journal PDGI Makassar, 2021)
Background: Gingival inflammation is not always caused by plaque buildup on the surface of teeth, but can also be caused by non-plaque factors and often shows a typical clinical picture. This review aims to describe various gingival diseases caused by plaque and non-plaque. Method: Review of various literature is conducted to find out various diseases in gingiva. A total of 38 literatures were collected from several electronic data sources using the combination search keywords